فاعلية تطبيق طريقة التدريب لإتقان المفردات فى الصف الرابع بالمدرسة الإبتدائية - Ulhasanah, Aulia; Mawardi; said, rukman abdul rahman (Al Ibrah: Journal of Arabic Language Education, 2020)
This study aims to find out how the Mastery of Class IV Vocabulary of Madrasah Ibtidaiyah Nurul Hikma Tolada North Luwu after using the Drill Method, Find out the Effectiveness of the Drill Method for the Mastery of Class IV Vocabulary of Madrasah Ibtidaiyah Nurul Hikma Tolada Luwu Utara. The results of this study show, Students' vocabulary mastery using the drill method has undergone many changes ranging from attitudes, learning enthusiasm and during the learning process, the interaction between students and teachers is very good. Students pay attention to the teacher's explanation and the class becomes calm. The application or use of the drill method is effective in improving the mastery of Arabic vocabulary in grade IV students of Madrasah Ibtidaiyah Nurul Hikmah Tolada. This can be evidenced by the increase in vocabulary mastery from cycle I to cycle II. The percentage of completeness of students' vocabulary mastery in the first cycle was 70% or as many as 7 students out of 10 students and in the second cycle there was an increase, namely with a percentage of 100%. From cycle I and cycle II, there was an increase in learning outcomes by 30%, thus in cycle II, learning outcomes were said to be complete and effective. تهدف هذه البحث إلى تطبيق طريقة التدريب لإتقان المفردات لمعرفة كيف إتقان المفردات فى الصف الرابع بالمدرسة الابتدائية نور الحكمة طولادا لووو الشمالية, بعد استخدام طريقة التدريب لمعرفة فاعلية طريقة التدريب لإتقان المفردات فى الصف الرابع بالمدرسة الإبتدائية نور الحكمة طولادا لووو الشمالية. أظهرت نتائج هذا البحث بعد تطبيق طريقة التدريب لتحسين إتقان المفردات العربية في الطلبة يمكن أن تعمل بشكل جيد. ويمكن ملاحظة ذلك في إدارة التعلم قبل الدورة حيث بلغ متوسط الدرجات 40.5 ثم زاد في الدورة الأولى بمتوسط الدرجات 70.5 وفي الدورة الثانية زاد بمتوسط الدرجات 80.5 وتم تضمينه في فئة ممتاز, تطبيق أو استخدام طريقة التدريب فاعلية لتحسين إتقان المفردات في التعلم اللغة العربية الطلبة الصف الرابع بالمدرسة الابتدائية نور الحكمة طولادا. يمكن إثبات ذلك لتحسين في إتقان المفردات من الدورة الأولى إلى الدورة الثانية. بلغت نسبة اكتمال إتقان الطلبة المفردات في الدورة الأولى 70٪ أو ما يصل إلى 7 الطلبة من أصل 10 الطلبة وفي الدورة الثانية كانت تحسين ، أي بنسبة 100٪. من الدورة الأولى والدورة الثانية ، كانت هناك تحسين في نتائج التعلم بنسبة 30 ٪ ، وبالتالي في الدورة الثانية ، قيل إن نتائج التعلم كاملة وفاعلية.